A new trade-off approach to photovoltaic power smoothing - Galarza, Jose; Condezo, David; Calcina, Armando; Saenz, Bartolome (International Journal of Electrical and Computer Engineering (IJECE), 2025)
Renewable energy sources, such as grid-connected photovoltaic systems, present a challenge due to the intermittent nature of solar irradiance. In this research, the authors have suggested an approach for irradiance profile smoothing based on different sample sizes of measurements. The analysis has been performed using experimental measurements based on the irradiance and temperature of the series smart pyranometers (SMP3) pyranometer manufactured by Kipp & Zonen. The power smoothing uses a variable window size to compensate for a flat and intermittent profile. The moving standard deviation has been used to evaluate the window size in different ranges. The evaluation focuses on days with higher irradiance variability and the results for the suggested approach show better performance than the smoothing process with a large or small window. The suggested approach reaches an autocorrelation index of 0.988, which is more than 6% with respect to the constant window size. Furthermore, the analysis shows that more than 50% of the data have variability in the moving standard deviation within a range of 1% and 25%, as with this approach a flexible window size helps the smoothing process. An estimation of photovoltaic power between constant and variable window size has been evaluated and a difference of less than 1.5% has been obtained.